Potential Post-Fire Impacts on a Water Supply Reservoir: An Integrated Watershed-Reservoir Approach - Basso, Marta; Mateus, Marcos; Ramos, Tiago B.; Vieira, Diana C. S. (Frontiers in Environmental Science, 2021)
Wildfires are an increasing threat in the Mediterranean region, causing frequent losses of goods and human lives. Not only are wildfires a concern due to their immediate effects on vegetation and soil, but they can also have substantial impacts on surface water quality. Approximately one-third of the world’s largest cities obtain their drinking water from forest catchments. The removal of vegetation and consequent runoff increase with a high concentration of ash and sediment often leads to increased nutrient and contaminant loads to downstream reservoirs, damaging the aquatic ecosystem and threatening human health. This study focused on the post-fire degradation of surface water in Castelo de Bode reservoir, a strategic freshwater supply for Lisbon’s metropolitan area (2,000,000 inhabitants), Portugal. Output data from the catchment model Soil and Water Assessment Tool were used as inputs to the CE-QUAL-W2 reservoir model. CE-QUAL-W2 was then calibrated for water level, temperature, nutrients, total suspended solids, chlorophyll-α, and dissolved oxygen. The post-fire impacts were assessed by adjusting land use features (curve number, crop vegetation management factor), and soil properties (soil erodibility) in the catchment model, considering the different impacts of fire (low, medium, and high severity). The reservoir model was able to perform temperature seasonality and stratification while a weak performance was found for chlorophyll-α probably for having considered only a group of algae. Simulations showed a deterioration of water quality at the dam wall during the first year after the forest fire. Nevertheless, contamination did not appear worrisome with regards to water quality standards likely due to the capability of the reservoir to attenuate inflow concentrations.